Lanthanide-doped nanoparticles conjugated with an anti-CD33 antibody and a p53-activating peptide for acute myeloid leukemia therapy. (June 2018) - Niu, Fan; Yan, Jin; Ma, Bohan; Li, Shichao; Shao, Yongping; He, Pengcheng; Zhang, Wanggang; He, Wangxiao; Ma, Peter X.; Lu, Wuyuan
Abstract: Roughly one third of all human cancers are attributable to the functional inhibition of the tumor suppressor protein p53 by its two negative regulators MDM2 and MDMX, making dual-specificity peptide antagonists of MDM2 and MDMX highly attractive drug candidates for anticancer therapy. Two pharmacological barriers, however, remain a major obstacle to the development of peptide therapeutics: susceptibility to proteolytic degradation in vivo and inability to traverse the cell membrane. Here we report the design of a fluorescent lanthanide oxyfluoride nanoparticle (LONp)-based multifunctional peptide drug delivery system for potential treatment of acute myeloid leukemia (AML) that commonly harbors wild type p53, high levels of MDM2 and/or MDMX, and an overexpressed cell surface receptor, CD33. We conjugated to LONp via metal-thiolate bonds a dodecameric peptide antagonist of both MDM2 and MDMX, termed PMI, and a CD33-targeted, humanized monoclonal antibody to allow for AML-specific intracellular delivery of a stabilized PMI. The resultant nanoparticle antiCD33-LONp-PMI, while nontoxic to normal cells, induced apoptosis of AML cell lines and primary leukemic cells isolated from AML patients by antagonizing MDM2 and/or MDMX to activate the p53 pathway. Fluorescent antiCD33-LONp-PMI also enabled real-time visualization of a series of apoptotic events in AML cells, proving a useful tool for possible disease tracking and treatment response monitoring. Our studies shed light on the development of antiCD33-LONp-PMI as a novel class of antitumor agents, which, if further validated, may help targeted molecular therapy of AML.